Mass public opinion: algorithmic colonisation and synthetisation of the public sphere - Carlos Saura García; Patrici Calvo (Revista CIDOB d'Afers Internacionals)
This paper examines the strategic change in the manipulation of public opinion through algorithmic colonisation, technological imperialism, data generation and the creation of synthetic content. This is utilised by government organisations, big tech corporations and economic powers to threaten the integrity of democracy via the alteration of the processes of rationalisation and meaning-making, as well as the communication flows involved, which leads to the appearance of social pathologies, anomalies and distortions in the digital public sphere. The aim of this paper is to show the main strategies related to disruptive digital technologies for the creation of meaning and the manipulation of public opinion and, especially, critique the impacts and challenges for public opinion and democracy underlying this new algorithmised, synthetised and mass democratic context.